CD8+ cells and small viral reservoirs facilitate post-ART control of SIV replication in M3+ Mauritian cynomolgus macaques initiated on ART two weeks post-infection. - Olivia E Harwood; Lea M Matschke; Ryan V Moriarty; Alexis J Balgeman; Abigail J Weaver; Amy L Ellis-Connell; Andrea M Weiler; Lee C Winchester; Courtney V Fletcher; Thomas C Friedrich; Brandon F Keele; David H O'Connor; et al. (PLoS Pathogens)
Sustainable HIV remission after antiretroviral therapy (ART) withdrawal, or post-treatment control (PTC), remains a top priority for HIV treatment. We observed surprising PTC in an MHC-haplomatched cohort of MHC-M3+ SIVmac239+ Mauritian cynomolgus macaques (MCMs) initiated on ART at two weeks post-infection (wpi). None of the MCMs possessed MHC haplotypes previously associated with SIV control. For six months after ART withdrawal, we observed undetectable or transient viremia in seven of the eight MCMs, despite detecting replication competent SIV using quantitative viral outgrowth assays. In vivo depletion of CD8α+ cells induced rebound in all animals, indicating the observed PTC was mediated, at least in part, by CD8α+ cells. With intact proviral DNA assays, we found that MCMs had significantly smaller viral reservoirs two wpi than a cohort of identically infected rhesus macaques, a population that rarely develops PTC. We found a similarly small viral reservoir among six additional SIV+ MCMs in which ART was initiated at eight wpi, some of whom exhibited viral rebound. These results suggest that an unusually small viral reservoir is a hallmark among SIV+ MCMs. By evaluating immunological differences between MCMs that did and did not rebound, we identified that PTC was associated with a reduced frequency of CD4+ and CD8+ lymphocyte subsets expressing exhaustion markers. Together, these results suggest a combination of small reservoirs and immune-mediated virus suppression contribute to PTC in MCMs. Further, defining the immunologic mechanisms that engender PTC in this model may identify therapeutic targets for inducing durable HIV remission in humans.